Mosquito Surveillance in Northwestern Italy to Monitor the Occurrence of Tropical Vector‐Borne Diseases. (November 2013) - Pautasso, A.; Desiato, R.; Bertolini, S.; Vitale, N.; Radaelli, M.C.; Mancini, M.; Rizzo, F.; Mosca, A.; Calzolari, M.; Prearo, M.; Mandola, M.L.; Maurella, C.; et al.
Summary: Mosquito‐borne arboviruses (MBV) represent an important health problem, causing diseases and deaths both in human and animals mainly in tropical and subtropical countries. In recent years, they have emerged also in temperate regions where they have caused epidemics. Of mounting concern among public health authorities in Europe are zoonotic mosquito‐borne viruses belonging to the Flavivirus genus. The aim of this study was to carry out active surveillance on mosquitoes in two regions of northwestern Italy (Liguria and Piedmont) to gain a better knowledge of the mosquito populations by identifying potential vectors of arboviruses and to investigate arbovirus infection. A network of 61 CO2 CDC traps was placed in the study area; sampling was conducted from May to October 2011. A total of 46 677 mosquitoes was collected, identified to species level, and classified according to their vector competence. Mosquitoes collected from 16 traps, selected according to risk‐based factors, were tested by biomolecular analysis to detect flavivirus infection. This study highlights the importance of entomological surveillance in northwestern Italy because most of the mosquitoes collected were found to have high vector competence. Moreover, the risk‐based virological surveillance allowed to detect the presence of mosquito flavivirus RNA, phylogenetically closely related to the MMV Spanish isolate, in three pools and USUV RNA in one pool in new areas where it has not been reported previously. The availability of continuous data on mosquito populations provides invaluable information for use in cases of an epidemic emergency. Maintenance of this integrated system for the next years will provide stronger data that can inform the design of a risk‐based surveillance for the early detection of the occurrence of outbreaks of tropical MBDs.